(untitled) - Addressing the legacy of agent orange in Vietnam (Washington DC, 2010)
On June 16th, 2010, members of The U.S.-Vietnam Dialogue Group on Agent Orange/Dioxin unveiled a comprehensive 10-year Plan of Action to address the toxic legacy of Agent Orange and other herbicides in Vietnam. The group called upon the U.S. and Vietnamese governments to join with other governments, foundations, businesses, and nonprofits in a partnership to clean up dioxin “hot spots” in Vietnam, and to expand humanitarian services for people with disabilities in that country.
Keywords: Dioxins,Agent orange,Herbicides,Thuốc diệt cỏ,Chất độc da cam